(untitled) (The Strategic Review for Southern Africa, 2020)
As is the case the world over, human trafficking remains a serious issue of concern amongst the Southern African Development Community (SADC) member states. At a time when most of the SADC states are confronted with slow economic growth, poverty and limited economic opportunities, several people continue to be forcibly or deceptively recruited and transported across borders for various purposes that include sexual exploitation, forced labour, slavery and/or removal of organs. This is despite the fact that most SADC countries are signatories to the United Nations Protocol to Prevent, Suppress and Punish Trafficking in Persons of 2000, especially Women and Children (the Palermo Protocol) which supplement the United Nations Convention against Transnational Organized Crime (UNTOC). However, SADC member states have been implementing a sundry of strategies in the form of policies, legislations, regional interventions and plans of action such as the 10 Year SADC Strategic Plan of Action on Combating Trafficking in Persons, especially Women and Children (2009-2019), in order to combat human trafficking in the region. With the use of primary and secondary data sources, this paper sought to evaluate the anti-trafficking strategies that have been implemented so far by SADC member states at national and regional level. It further identifies the challenges being encountered, as well as opportunities presented within the regional and global networks for fighting human trafficking. On the strength of the research findings, appropriate suggestions are made to enhance the success of strategies being implemented in the SADC region in particular, and other parts of Africa in general.